Effects on natural regeneration of woodland in a dehesa system grazed by Avileña-Negra Iberica breed - Rodríguez R.; López-Carrasco C.; Zuzuarregui J. (Dynamics and sustainability of Mediterranean pastoral systems, 1999)
Effects on concentrated calving against continuous calving and different supplementation levels on cattle in a dehesa system have been studied. In these experimental conditions we considered necessary to evaluate grazing effects on natural regeneration of holm oak (Quercus rotundifolia) and cork oaks (Quercus suber).
9. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 1997/11/26-29, Badajoz (Spain)